(untitled) (American Journal of Islam and Society, 2023)
According to Yusuf al-Qaradawi – a prominent Muslim jurist of the contemporary period, the jurisprudence of priorities is intended to mitigate excess and negligence in legal reasoning. This article examines the fundamental principles of the jurisprudence of priorities as propounded by Yusuf al-Qaradawi in relation to the foundational sources of Islamic law. The purpose of this article is to dissect the constituent legal principles of the jurisprudence of priorities and critically evaluate their validity and coherence against the textual and rational evidences of Islamic law. This article argues that the fundamental principles of the jurisprudence of priorities are validated in the sources of Islamic law, and do facilitate the mitigation of excess and negligence in legal reasoning.